Role of Natural Gas Discoveries in forming the Geopolitics of Eastern Mediterranean Basin - Dayoub, Mohammad Maan; Alio, Mustafa (Latakia University Journal - Economic and Legal Sciences Series, 2020)
Since 2009, Eastern Mediterranean basin has attracted the attention of the international energy markets following its massive offshore gas discoveries. Given the pairing relation between the economic and political behaviors in international relations, it is not expected for this region to gain the access into international gas markets, mainly the market of European Union, in isolation from the fierce conflict of interests of regional parties, particularly amid an environment of geopolitical tensions. This paper aims to study the behaviors of the countries of Eastern Mediterranean that are actively involved in actual investment of the offshore fields (Turkey, Greece, Cyprus, Egypt and “Israel”), based on the strategies, treaties, conventions and actions of these parties, i[1]n order to reach comprehension of the geopolitical reality of the region. The study showed that the discovered gas reserves did not contribute to pave the way for an extensive cooperation between regional parties; nor to eliminate their traditional tensions. In contrary, gas discoveries has enhanced the geopolitical tension and increased tendencies towards escalation between the growing alliances of Greece, the Republic of Cyprus, “Israel” and Egypt on one side; Turkey and Northern Cyprus on the other side. شغلت منطقة حوض شرق البحر المتوسط اهتمام أطراف سوق الطاقة الدولي بعد تتالي الاكتشافات الغازية الضخمة ضمنها منذ عام 2009. ونظراً لارتباط السلوك الاقتصادي بالسلوك السياسي في العلاقات الدولية، فإنه من المفترض ألا تمر عملية دخول هذه المنطقة ضمن سوق الطاقة الدولي (وعلى رأسه سوق الاتحاد الأوروبي) بمعزل عن صراع مصالح دول المنطقة في تقاسم حصصها من الغاز في بيئة من الاحتقان الجيوسياسي. هدف هذا البحث إلى دراسة سلوك أطراف منطقة شرق المتوسط ذات المشاركة الفعلية في العمليات الاستثمارية والتطورات السياسية للاكتشافات الغازية البحرية المتمثلة بكل من (تركيا، اليونان، جمهورية قبرص، مصر والكيان الصهيوني)، وذلك بالاستناد إلى الاستراتيجيات والمعاهدات والاتفاقيات والتطورات المعلنة ذات الصلة لهذه الأطراف، وصولاً إلى التوصيف الدقيق لواقع الجغرافية السياسية المستند إلى احتياطيات الغاز ضمن المنطقة. أظهرت الدراسة عدم مساهمة احتياطيات الغاز المكتشفة في تحقيق التعاون وإزالة الخلافات التاريخية بين هذه الاطراف، وبالتالي تعزيز حالة التوتر الجيوسياسي وميله نحو التصعيد، وذلك بين التحالفات المتنامية بين اليونان وجمهورية قبرص والكيان الصهيوني ومصر من جهة، مقابل تركيا و"قبرص الشمالية" من جهة ثانية.